El 11 de septiembre, ¿una catarsis para todos? - Mera Fernández, Montse (Estudios sobre el Mensaje Periodístico, 2002)
After September 11th, once we’re overcome the shock of being present at the terrorist attacks which seemed to be a science-fiction show, many people thought that such date would determine a before and after stage of the contemporary history. Many thought about the drastic change that economy and politic would experience as well as the influence on culture, religion and journalism. At newspaper offices all around the world both journalists and social communication specialists reflected on the happenings and asked themselves what such events would involve for their profession. After several years of an informative labour which seemed to get trivial, many people thought that together with the twin towers, this way of tackling the information had collapsed too.